Efektivitas Sanksi Administrasi Dalam Mencegah Pencemaran Sungai - Stella Stella; Yuwono Prianto (Jurnal USM Law Review)
The purpose of the research is to analyze the effectiveness of compliance with the Environmental Law and the impact of administrative sanctions on companies violating river pollution regulations. The urgency of this research lies in the need to analyze the effectiveness of administrative sanctions in curbing environmental violations by textile companies, which cause river pollution in Indonesia, to provide a deterrent effect and raise awareness of the importance of maintaining environmental quality. The number of environmental violations by textile companies that cause river water pollution is the reason behind the preparation of this research. This is very important because scientific studies serve as an analysis and information for the general public and input for the government so that it can become a concentrated issue and achieve a quick and precise resolution. The type of this research is normative juridical. The novelty in the research that the author presents is the author's intention to understand the effects of the use of administrative sanctions. The results of this study indicate that the effectiveness of administrative sanctions is considered to provide a deterrent effect on the perpetrators/parties who pollute the river water. However, there is a need to further enhance the administrative sanctions given to achieve a more significant impact. Additionally, it is also noted that there is a need to improve the quality of supervision and the integrity of law enforcement officers to create better and more optimal environmental law enforcement.